18F-Fluorodeoxyglucose (FDG)-positron emission tomography/computed tomography in mucosa-associated lymphoid tissue lymphoma: variation in 18F-FDG avidity according to site involvement. Issue 12 (2nd December 2015) - Park, Seol Hoon; Lee, Jong Jin; Kim, Hye Ok; Lee, Dong Yun; Suh, Cheolwon; Jung, Hwoon-Yong; Choi, Kee Don; Kim, Do Hoon; Huh, Jooryung; Ryu, Jin-Sook
Abstract : The purpose of this study was to determine the 18 F-FDG avidity of MALT lymphoma and the additional utility of 18 F-FDG PET/CT in MALT lymphoma staging. Pretreatment 18 F-FDG PET/CT scans of 222 patients with 227 MALT lymphoma lesions were retrospectively analyzed. 18 F-FDG avidity of lesions was noted in 28%. The proportion was lower for gastric MALT lymphomas than for non-gastric lesions (9% vs. 60%, p < 0.0001) and higher for mass-forming lesions than for superficial lesions (82% vs. 2%, p < 0.0001). 18 F-FDG PET/CT showed the presence of additional lesions in 23 patients: four of six true-positive lesions had 18 F-FDG avid primary lesions, and 15 of 17 false-positive lesions had 18 F-FDG-non avid lesions. 18 F-FDG avidity differed according to the location and gross morphologic characteristics of the MALT lymphoma. Most gastric MALT lymphomas were superficial and had low 18 F-FDG avidity. For staging, 18 F-FDG PET/CT can be helpful mainly for 18 F-FDG avid primary MALT lymphomas.